Benefits of creatine in performance and muscle strength development (Research, Society and Development, 2022)
Introduction: Currently, the demand for supplements to increase physical performance has grown a lot, in view of this Creatine (Cr), is a supplement that has become one of the most used nutritional ergogenic resources in recent decades. This was due to a possible improvement in sports performance or in gym training. Methodology: Descriptive in which we seek to highlight the benefits and harms of using creatine in strength training and in improving physical conditioning recorded in the national literature. Results and Discussions: Creatine supplementation is an ergogenic resource that has been used to improve sports performance and muscle strength in high-intensity exercises. However, its effects on the improvement of muscle strength are still the subject of much discussion among researchers. Conclusion: In this way, adequate supplementation regarding the prescribing professional and prescribed amounts, can promote physical benefits to individuals, such as: increase in maximum strength, power and muscular endurance, motor coordination, speed, agility, balance and the prevention and injuries that together with activities that demand strength and high intensity, being then, a potential for the increase of body mass. Therefore, it is concluded that creatine supplementation in strength training properly, with the help of the nutritionist and physical educator, exerts effects that can contribute to periodized strength training, improving the performance of muscle strength and lean mass.